KONSTRUKSI IDEOLOGI TAFSIR WEBSITE : STUDI ANALISIS TERHADAP KONTEN TAFSIR MODERASI BERAGAMA DALAM TANWIR.ID - Nisa Kamila Labibah; Fathonah, Siti (Academic Journal of Islamic Principles and Philosophy, 2025)
The interpretation of the Qur'an has continuously evolved over time. The transition of Qur'anic exegesis from print media to digital media presents its own challenges and issues within the field of tafsir studies. Additionally, there is a potential risk of manipulation and the deliberate insertion of ideological influences by website owners. The objective of this research is to describe the ideological construction promoted by Tanwir.id. The central issue in this study lies in how the Tanwir.id website constructs its ideology in shaping the discourse on Qur'anic exegesis. This research is a field study with a descriptive-analytical approach. The data analyzed using Berger and Luckmann's social construction theory, focusing on externalization, objectivation, and internalization. The findings indicate that in the externalization process, interactions and self-expression of contributors take place within the reality of the Tanwir.id website. The objectivation process as a form of social interaction is evident through institutionalized intersubjective dialogues, while the internalization process is reflected in the contributors' efforts to identify themselves with the content standards established by Tanwir.id. The ideology promoted by Tanwir.id is a moderate-comprehensive ideology.